2007
DOI: 10.1145/1227134.1227136
|View full text |Cite
|
Sign up to set email alerts
|

Obstacle avoidance during walking in real and virtual environments

Abstract: Immersive virtual environments are a promising research tool for the study of perception and action, on the assumption that visual-motor behavior in virtual and real environments is essentially similar. We investigated this issue for locomotor behavior and tested the generality of Fajen and Warren's [2003] steering dynamics model. Participants walked to a stationary goal while avoiding a stationary obstacle in matched physical and virtual environments. There were small, but reliable, differences in locomotor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
84
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 29 publications
14
84
4
Order By: Relevance
“…By using standard models of human locomotion [1,2], it is possible to obtain an expected reference path to each of the targets. Once the user starts moving, the observed movement can be compared to the simulated reference trajectories and a prediction can be made.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…By using standard models of human locomotion [1,2], it is possible to obtain an expected reference path to each of the targets. Once the user starts moving, the observed movement can be compared to the simulated reference trajectories and a prediction can be made.…”
Section: Related Workmentioning
confidence: 99%
“…From the gathered data , we calculate P(G ∈ G i |τ i ) (see Table 1) and determine the probability as defined in equation (2).…”
Section: Eye Tracking Realizationmentioning
confidence: 99%
See 1 more Smart Citation
“…E.g. [4,5] present dynamic walking models which can generate natural human walking trajectories numerically. Hence, we designed a VE that constrained the walk paths 1 www.oculusvr.com 2 www.unity3d.com so that the trajectories could be predefined.…”
Section: Virtual Environmentmentioning
confidence: 99%
“…As in the real world, depth spans are often compressed relative to frontal spans [10]. Additionally, Fink et al [5] showed differences in trajectories between real and virtual movements, indicating greater uncertainty about object positions.…”
Section: Distance Perception In Virtual Environmentsmentioning
confidence: 99%